Viabilidade ambiental na indústria de envase de água mineral - Lopes, Jessica Rafaelly Almeida (Universidade Federal Rural do Semi-Árido, 2019)
The extraction of mineral water has been leveraged in recent years due to the properties present in its composition and the benefits associated with human health. With this, the objective of this work was to verify the environmental viability of the implantation of a mineral water container industry in Icapuí/CE. The study was carried out based on the identification of environmental impacts. A matrix cell was used to classify the impacts arising from the installation and operation phase of the enterprise in terms of character, order, magnitude and duration, and thus propose mitigating measures to mitigate the environmental impacts listed and then apply good environmental practices within the stages of the company's production process. Therefore, from the survey, we listed 26 impacts, among which we have: decharacterization of the landscape, suppression of the vegetation cover, removal of some specimens of the fauna, besides the use of local labor and the generation of employment and income. In order to mitigate these adverse effects, it was possible to present some mitigating measures such as: to elaborate the monitoring and management program of the fauna, to carry out deforestation only in the useful area for the project, as well as training and skills that enhance the activities developed by the company. Already as an application of good environmental practices it was possible to suggest the following techniques: partnerships with recycling cooperatives, supplying the bottles as raw material for other productive processes, such as using the water for irrigation of the green area and supplying the boxes of the bathrooms . Therefore, the environmental feasibility studies of an enterprise are of fundamental importance, since it was possible to predict the adverse effects of the activity in the environmental compartments and consequently to expose mitigating measures and good environmental practices that make possible the installation and operation of the water container industry mineral.
Keywords: Degradação ambiental; Impactos ambientais; Gestão ambiental.; Environmental degradation; Environmental impacts; Management environmental.; ENGENHARIAS::ENGENHARIA SANITARIA